Pré-Natal da gestante de risco habitual: potencialidades e fragilidades na consulta. - SILVA, Andressa Arraes (2018)
Prenatal care has as principle to ensure a complete care to the pregnant woman's health and her baby, and the organization of routine and procedures to be developed during prenatal care involves the availability of various resources that range from the presence of professionals to the access to the materials needed for the prenatal consultation. The consultation, which is part of prenatal care, should be developed through methods that seek to promote a woman and the baby quality of life during pregnancy. The research had as objective to know the potentialities and weaknesses in the operationalization of the prenatal consultation to the pregnant women of habitual risk. A descriptive study was carried out with a qualitative approach from July to September 2017, with twenty pregnant women and six professionals who performed prenatal care in a sanitary district of São Luís - Maranhão. This study is linked to the research Retraining Prenatal Care in São Luís, approved by the Research Ethics Committee of the Federal University of Maranhão. For data collection, an instrument was used as a check list, a questionnaire and a semi-structured interview. The data were described and organized into thematic categories according to the Bardin Content Analysis and analyzed in the legal provisions of the Ministry of Health regarding prenatal care. It was possible to abstract three thematic categories: the potentialities that humanize prenatal care; the weaknesses found in the trajectory; factors that contribute to the satisfaction x dissatisfaction of the pregnant woman. Although the majority of the pregnant women are satisfied with the prenatal care, the studied district is unsatisfactory in several aspects related to the parameters of prenatal adequacy, recommended by the Ministry of Health, since the weaknesses pointed standed out the potentialities.